An analytical framework for improving the strategical impact of customer collaboration in innovation - Kayakutlu, Gulgun; Koh, S.C. Lenny (Inderscience Publishers, 2008)
Information gathered through customer collaboration has an improving importance in innovation strategies. The objective of this study is to enhance the impact of customer information in a variety of innovation fields by implementing the 'best fit' customer relationship strategy in a small company. The investigation of the alternative innovation determinants and customer relation strategies has led in defining a new framework for the selection and progress of the customer relation strategy with the focus of innovation. A combination of the Analytical Hierarchical Processing (AHP) and Delphi methods is used in designing the decision framework, which is evaluated by a case study run on five small companies representing design-based and food industries. It is observed that small companies are enthusiastic in applying innovations in various fields but are not yet aware of the importance of customer collaboration. Besides, innovation strategies are differentiated by the age and business focus of the company. This paper will be stimulating for the small companies in designating innovation strategies.